Evaluation of nutritive value, in vitro fermentation, and antimethanogenic potential of native South African macroalgae species - Du Toit, Lindique (University of Pretoria, 2024)
Dissertation (MSc (Agric) Animal Science: Animal Nutrition)--University of Pretoria, 2024.